(3ajV GdbOjQ TQM GdLGeY GdUZjQs - (3GdMOGOj GdbGgQj GdefGhj, Rjf GdOjf, eMeO YHO GdQADa Hf JGL GdYGQajf Hf Ydj Hf Rjf GdYGHOjf, J (B1031 (3g`s ((3GdLGeY GdCehjs)
(3ChdgG (B:s
(3HYO GdHSedI ; (B( (3eG ef eSde jOYh dCNjg HXgQ GdZjH (B) (3Cj aj ZjHI GdeOYh dg (B( (3EdG bGd Gdedc (B) (3haj QhGjI Gdehcd Hg (B( (3hdc HeKdg (B) (3HcSQ Gdeje hSchf GdeKdKIs
(3BNQgG (B:s
(3cdGgeG (B( (3Yf CHj gQjQI (B) (3bGd GdJQePj ZQjH dG fYQag EdG ef MOjK ehSi GHf YHjOI hgh QhGg GfJgi hbGd GdPgHj aj GdePgH ehSi GHf YHjOI QhGg GfJgis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6 / 204s
(3eYLe GdeDdajf (B2 / 143s
(3cTa GdXfhf (B1 / 561s
(3GdHOQ GdWGdY (B1/ 357s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK hGdeUWdMs